Autism : a social skills approach for children and adolescents - Aarons, Maureen. (Winslow, 1998)
Assessment. Setting the scene for intervention. Pre-school intervention. Infant-level intervention. Junior-level intervention. Intervention with older children & adolescents. Further practicalities of running social skills groups.